Julius Pflug (1499-1564) et la crise religieuse dans l'Allemagne du XVIe siècle : essai de synthèse biographique et théologique - Pollet, J. V. (Jacques V.) (Studies in medieval and Reformation traditions, 1990)
This book retraces the life and work of Julius Pflug (1499-1564), humanist, man of the church and diplomat. Born from a family of Saxon knights, Julius Pflug was educated mostly in Italy under such masters as Amaseo and Bonamico - hence his excellent Latin style, which even Erasmus admired. During his ecclesiastical career he was provost of Zeitz, dean of Meissen and bishop of Naumburg-Zeitz. As such he attended the Council of Trient in its second period (1551/52). Pflug has attracted the attention of historians mostly on account of his role in the so-called Colloquies of religion designed to put an end to the religious schisms which divided the Church as well as the Empire: Regensburg (1541 and 1546), Worms (1557), over which he presided. After the Peace of Augsburg (1555), he was only able to save the remnants of Catholicism in his own diocese. The interest of this biography is twofold: firstly, it allows us to survey the progress of the Lutheran Reformation, which Catholic apologists such as Pflug, Gropper, Witzel were unable to stop. Secondly, as Pflug was entangled in all the political and religious events of his time, this book reveals a wide range of personalities in Saxony and Germany, and imperial circles at large. On the other hand, if Pflug's work belongs to a period of transition, it retains through its irenic character an interest of topicality, while opinion is more sensitive to conciliation than to opposition of confessional differences. Following the analysis of the sources due to the publication of Pflug's Correspondence by the same author (published by Brill 1969-1982), this monograph gives a more synthetic view, which addresses itself to a larger public. Ce livre est une biographie de Julius Pflug (1499-1564), humaniste, homme d'Eglise et diplomat. D'une famille de chevalier saxons, Julius recut une formation humaniste auprès des maîtres italiens; son latin est d'une pureté classique qu'admirait même Erasme. Il eut un carrière ecclésiastique: prévot de Zeitz, doyen de Meissen, enfin évêque de Naumburg-Zietz. A ce titre, il assista au Concile de Trente dans sa 2ème période. L'histoire a retenu surtout son rôle dans les Colloques de religion, où il seconda la politique impériale de rapprochement entre Catholiques et Luthériens: Ratisbonne (1541 et 1546), Worms (1557). Depuis la Paix d'Augsbourg (1555), il ne put que tenter de sauver les restes cu catholicisme dans son diocèse. L'intéret de cette biographie est double: c'est d'abord de nous faire assister au progrès de la Réforme luthérienne que les apologistes catholiques, tels que Pflug, Gropper, Witzel, ne parvinrent pas à endiguer; ensuite, comme Pflug a été mêlé à tous les événements politiques et religieux de son temps, nous sommes mis par ce biais en relation avec les personnalités marquantes, tant en Saxe qu'en Allemagne et dans les cercles impériaux. Par ailleurs, si l'oeuvre de Pflug appartient à une période de transition, elle regagne par son irénisme un intérêt d'actualité, alors que l'opinion est plus sensible à la conciliation au'à l'opposition des différences confessionelles. C'est pourquoi à l'analyse des sources fournies par la publication de la Correspondance de Julius Pflug (6 vol.) devait succéder la synthèse sous forme d'étude à la fois biographique et théologique. Celle-ci s'adresse à un public élargi, aussi bien spécialistes de la Réforme que lettrés et étudiants intéressés par l'histoire allemande à l'orée de l'âge moderne.